Nutrition characteristics and delivery in relation to 28-day mortality in critically ill patients - Abdul Raheem, Asiya (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: The limited data regarding nutrition characteristics and the delivery of critically ill patients in South Asia is intriguing. This study was conducted to investigate the nutrition characteristics and delivery in relation to 28- day mortality in mechanically ventilated patients. Methods: This prospective observational study was conducted in the intensive care unit (ICU) of the Maldives government referral hospital. Data about nutrition characteristics and delivery were collected from the ICU charts, and each patient was followed for a maximum of 28 days. Results: We recruited a total of 115 patients (mean age: 61.57±17.26 years, 52% females, mean BMI: 25.5±6.19kg/m2), of which 61 (53%) of them died within 28 days of ICU admission. Mean energy intake was 681.15±395.37 kcal per day, and mean protein intake was 30.32±18.97g per day. In the univariate logistic regression analysis, length of stay in ICU (OR = 0.950, 95% CI: 0.908 – 0.994, p = 0.027), and received intervention by a dietitian (OR = 0.250, 95% CI: 0.066 – 0.940, p = 0.040) were associated with 28-day mortality. None of the factors in the multivariate regression analysis remains significant when adjusted for sex, SOFA total score, daily energy and protein dosage. Conclusion: 28-day mortality was much higher in this study than in similar studies in South Asia, Asia and around the globe. None of the variables was significantly associated with 28-day mortality in the multivariate logistic model. However, there was a trend towards higher mortality for patients with shorter length of stay in the ICU, larger mean gastric residual volume, and no intervention by a dietitian.